Food Supply Chain through Ongoing Evolution: Lessons from Continuous Transformations - Thomé, Karim Marini; Bourlakis, Michael; Guarnieri, Patricia (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Considering their constant evolution and transformation, in this Special Issue, several authors provide contributions bringing light to different aspects related to food supply chains, based on several conceptual frameworks, agri-food areas and contexts, as well as multiple levels of analysis. In this book, the promotion of win-win investments in Brazil's Agribusiness is discussed, as well as how family farmers can thrive in commodity markets in long agribusiness supply chains. The Logic of Collective Action for Rural Warehouse Condominiums, which is a new configuration in the agribusiness supply chain, is also addressed. In this book, the Brazilian Jabuticaba Supply Chain is analyzed through a multi-methodological approach. The role of logistics in food-waste reduction for wholesalers and small retailers of fruits and vegetables is also presented. The issue of transparency in global agribusiness in the Brazilian soybean supply chain is discussed based on companies' accountability. Finally, the transformation of the food supply chain through technology and future research directions are highlighted in this Special Issue. This book aims to assist students, researchers and practitioners interested in the evolution and transformations of food supply chains.